2007
DOI: 10.1109/tec.2006.889624
|View full text |Cite
|
Sign up to set email alerts
|

HVDC Connection of Offshore Wind Farms to the Transmission System

Abstract: This paper presents a technical and economic analysis to evaluate the benefits and drawbacks of grid connecting offshore wind farms through a dc link. A first case, concerning a 100-MW wind farm, is thoroughly investigated and cases of larger wind farms (200 and 500 MW) are presented. Three different transmission solutions are compared: 150-kV ac, 400-kV ac, and highvoltage dc based on voltage sourced converters (VSC-HVDC). After a brief overview of the features of these connection solutions, the related opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
379
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 642 publications
(383 citation statements)
references
References 3 publications
1
379
0
3
Order By: Relevance
“…Di erent studies have shown the capability of VSC-HVdc enhancing the stability of power systems [7], [8], providing voltage support [9], [10] and its application in the connection of wind farms [11], [12], just to mention some references.…”
Section: Vsc-hvdc On Power Systemsmentioning
confidence: 99%
“…Di erent studies have shown the capability of VSC-HVdc enhancing the stability of power systems [7], [8], providing voltage support [9], [10] and its application in the connection of wind farms [11], [12], just to mention some references.…”
Section: Vsc-hvdc On Power Systemsmentioning
confidence: 99%
“…In this case, OWF cannot contribute to the onshore fault. In addition, VSC-HVDC can provide fast control of both active and reactive power independently [6,8].…”
Section: Introductionmentioning
confidence: 99%
“…For Back-toBack HVDC systems, the voltage is controlled using an unique local control that maintain constant ot [13]. For M-HVDC applications other controllers and controllers coordination are used [14], but the most studied controller is the droop controller.…”
Section: Introductionmentioning
confidence: 99%